Static evaporation of hydrocarbons and measures to prevent this process - Спаська, А. О. (Problems of Environmental Biotechnology, 2013)
The effect of hollow glass microspheres layers barrier on the evaporation rate from the surface of liquid individual hydrocarbons and mixtures was studied . It was found that the microspheres layers application does not protect, but increases evaporation of individual hydrocarbons C5-C10.